Validitas Media Pembelajaran Berbasis Vlog pada Muatan Bahasa Indonesia di Sekolah Dasar - M Rijali; Yudha Adrian (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
Vlogs are one of the alternative learning media used in Bahasa Indonesia lessons. This media is used to help android smartphones by the internet. Vlog-based learning media is embedded through the android application. The objective of this research to produce valid Vlog-based learning media on Bahasa Indonesia content in elementary schools. The development research model is the ADDIE development model (1990): 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The subjects in the study were expert validators and users. Due to the Covid-19 pandemic, the trial was not. The data analysis technique used was quantitative from a questionnaire sheet, a qualitative test from comments and suggestions from research subjects. The results of this study are the validity of material experts by 86% (very valid), media by 91% (very valid), from linguists 96% (very valid) and teacher experts by 76% (valid) and students by 80% (valid).